SOCIO-ETHICAL ISSUES SURROUNDING CAESAREAN SECTION BIRTHS IN AFRICA - Yitambe, Andre; Kibaara, Rucha Kenneth; Warutere, Peterson (International Journal of Research -GRANTHAALAYAH, 2018)
In the last decade, a number of studies have questioned the practice of caesarean section birth in obstetrical practices in Africa. Medical sociologists and anthropologists have considered caesarean section as a medicalization of social events. We are not assuming that it is true of false. The transformation of social events into medical indications rises ethical issues in the provision of healthcare in Africa. In this paper, we especially used the case of caesarean section birth to explore the transformation of social events into medical indications in Africa. Caesarean sections by choice interrogates the obstetrical practices. This paper examines the socio-ethical issues in caesarean section in Africa. We considered some underlying factors: medicalization of the society, informed consent, biotechnology, demand inducement, consumer-inducement demand and the health market-driven economy. This was desk-based study. A review of secondary data and literatures relative to caesarean section births in Africa were used for discussion. Findings from literatures revealed that a number of considerations have to be taken such as: demand inducement and information asymmetry, defensive and corporate medicine, medical power, consumer induced demand and health market driven economy. The findings informed health regulators on demand and supply sides of caesarean sections.